Atenção compartilhada e crianças pequenas com autismo: ensino de resposta e verificação da emergência da iniciativa - Morais, Maria Rafaela Fernandes de (Universidade Federal de São Carlos, 2024)
Joint attention refers to a set of behaviors that allow an individual to engage with a social partner and an object of common interest. The literature on child development considers that the ability to share attention contributes to the development of language and other more complex behaviors. Children with autism tend to present more significant deficits in joint attention than typical children. In this sense, it is crucial to develop objective measures to assess and intervene early in behavioral deficits that impact the development of this population. The present research aimed to teach shared attention response behaviors and verify the emergence of the initiative. Three children with Autism Spectrum Disorder, aged between 4 and 5 years, participated in the research. A multiple-probe design was adopted, and the Baseline and Probe measurements were adopted, and the teaching procedure employed adaptations of three tasks from the Early Social Communication Scale (ESCS). The results indicated that the three children learned to respond to shared attention for the three tasks, but there was no emergence of the initiative to share attention. The procedure was efficient in teaching the behaviors of responding to shared attention, however, new studies must be carried out to analyze proximal and distal responding in tasks and their implications for the emergence of new performances.
Joint attention and young children with autism: teaching response and verifying the emergence of the initiative
Keywords: Atenção compartilhada; Procedimento de ensino; Autismo; Criança; Shared Care; Teaching procedure; Autism; Child; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO DESENVOLVIMENTO HUMANO